EL SUFIJO GRIEGO -ΩΔHΣ: ORIGEN, VALORES Y FORTUNA LITERARIA - de la Fuente Ruiz, Samuel (Myrtia, 2002)
In this paper I discuss the origin of the suffix -ώδης and its literary use from Homer to the 4th century B.C. With regard to the former, I propose that the suffix -ώδης is the phonetic result of the sequence *-o-h3ed-es- in compounds whose first element was thematic; we find this same phonetic result in compounds whose first element was athematic, because -o- probably spread to all adjectives in -ώδης in its function of connection vowel (cf. also suffix -όεις). I propose also that the Greek -s -/ -es - and the Latin -s -/-os - are a suffix in different vocalic degrees: that is why some Indo-European languages only have words with a radical *od -. More speculative is the hypothesis which we suggest about the connection between adjetives in -ώδης and the ones in -ής: perhaps the adjetives in -ώδης were originally compounds in -ής (as εὐγενής) constituted over a lost proto-Greek sustantive *odōs ; this theory faces the position of the accent in -ώδης in historical Greek. As for the literary development of this suffix, I verify that the first Greek evidence -epic poetry- suggests to us that -ώδης perhaps operated originally as a second element of compounds. Later the suffix values were gaining ground until the Ionic prose: at that moment the scientific prose of medicine multiplied by hundred the use of these adjectives, most of them technicisms of new creation. Attic literature inherited from the Ionic one the massive use of suffix -ώδης, but its distribution in the different prose genres is unequal: scientific prose makes room for an enormous amount of these derivatives in -ώδης, whereas on the other hand oratory scarcely uses a few of them; in between, we have historiography and philosophy.